2017
DOI: 10.3390/ijms18091863
|View full text |Cite
|
Sign up to set email alerts
|

SMAD2 Inactivation Inhibits CLDN6 Methylation to Suppress Migration and Invasion of Breast Cancer Cells

Abstract: The downregulation of tight junction protein CLDN6 promotes breast cancer cell migration and invasion; however, the exact mechanism underlying CLDN6 downregulation remains unclear. CLDN6 silence is associated with DNA methyltransferase 1 (DNMT1) mediated DNA methylation, and DNMT1 is regulated by the transforming growth factor beta (TGFβ)/SMAD pathway. Therefore, we hypothesized that TGFβ/SMAD pathway, specifically SMAD2, may play a critical role for CLDN6 downregulation through DNA methyltransferase 1 (DNMT1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Our results were in line with previous studies, indicating an oncogenic role of CLDN6. 24 26 However, the exact mechanisms remain poor. Significantly, a former report has demonstrated that enhanced proliferation and migration of tumor cells may be caused by the altered change in ionic microenvironments in the lateral membranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were in line with previous studies, indicating an oncogenic role of CLDN6. 24 26 However, the exact mechanisms remain poor. Significantly, a former report has demonstrated that enhanced proliferation and migration of tumor cells may be caused by the altered change in ionic microenvironments in the lateral membranes.…”
Section: Resultsmentioning
confidence: 99%
“… 6 8 CLDN6 may suppress migration and invasion of cancer cells via EMT inhibition. 26 However, the mechanisms that could explain how CLDN6 regulate cell proliferation rate, migration, and invasiveness still remain to be revealed.…”
Section: Resultsmentioning
confidence: 99%
“…The overexpression of claudin-6 was showed to inhibit migration and invasion of MCF-7 cells [104]. Lu et al demonstrated that SMAD2 causes downregulation of claudin-6 by DNA (cytosine-5)-methyltransferase 1 (DNMT1)-mediated DNA methylation, which results in increased migration and invasion of breast cancer cells [105]. In addition, research has shown that estrogen receptor β (ERβ) plays an anti-cancer role in breast cancer, and Song et al demonstrated that this effect is mediated by claudin-6 [106].…”
Section: Claudins In Breast Cancermentioning
confidence: 99%
“…Similar to other SMADs, SMAD2 serves a role in the transmission of extracellular signals from TGF-β ligands into the cell nucleus and mediates cell proliferation, apoptosis and differentiation (45). The TGF-β-SMAD2/3 signaling pathway is involved in epithelial-mesenchymal transition in several malignant tumors, including hepatocellular carcinoma (46), breast cancer (47) and colorectal cancer (48). In addition, SMAD2 also contributes to PE initiation (49).…”
Section: Discussionmentioning
confidence: 99%